2013
DOI: 10.1177/0731684413500858
|View full text |Cite
|
Sign up to set email alerts
|

Investigating bearing strength of pin-loaded composite plates in different environmental conditions

Abstract: Composites are subjected to different working environments when they are employed. In this study, the bearing strength and failure modes of composite-pinned joints subjected to various types of environments for different exposure times are investigated, experimentally. The specimens were divided into five categories which include cold environment, hot environment, humid environment, seawater environment, and room temperature. The test results were carried out after 1 and 2 months of exposure to different envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Esendemir and Cabioglu [24] showed that different environmental aging conditions do not modify the failure modes (i.e., net tension, shear-out, bearing, and mixed) for woven glass epoxy pinned composites. Nevertheless, they evidenced that the bearing strength of the joints is noticeable affected by the applied environment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Esendemir and Cabioglu [24] showed that different environmental aging conditions do not modify the failure modes (i.e., net tension, shear-out, bearing, and mixed) for woven glass epoxy pinned composites. Nevertheless, they evidenced that the bearing strength of the joints is noticeable affected by the applied environment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The same material was kept in the seawater with respect to one and two months in the other study. 18 The bearing strength reduced by a maximum of 10.71% and 17.91% for one and two months, respectively. The bearing strength of specimens immersed in seawater decreases its strength compared to a specimen immersed in rainwater.…”
Section: Resultsmentioning
confidence: 99%
“…As already stated, several papers have been focused on the bearing behavior of fiber-reinforced, polymer-based materials. Nevertheless, a further relevant aspect which has attracted increasing attention in the last few years is the evaluation of joints' durability; i.e., the knowledge of how the bearing performance can be modified when composite joints are exposed to aggressive environments, such as marine ones [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Esendemir and Cabioglu [20] compared the effects of various types of environments on the bearing strength and failure modes of woven glass epoxy pinned composites. In particular, they exposed specimens (at varying edge distance to hole diameter and specimen width to hole diameter ratios) to a cold environment (i.e., −18 • C), hot environment (i.e., 30 • C), room temperature (i.e., 21 • C), humid environment (i.e., 70% RH) and seawater environment for a period of 2 months.…”
Section: Introductionmentioning
confidence: 99%